Faktualizm Davida Armstronga - Firszt, Dawid (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
In my article I present David Armstrong's stance on properties, relations, particulars and states of affairs. I introduce this categories to show, at the most general level, his metaphysical system called factualism. My article consists of four parts, in each one I characterize following categories: 1. Properties 2. Relation 3. Particulars 4. States of affairs. I also discuss Armstrong's arguments considering the nature of those categories and their role in his philosophy. Also, I try to emphasis differences between Armstrong's factualism and other contemporary metaphysical positions (Bundle theory and Trop theory).